Protecting traditional knowledge lessons from global case studies - Wright, Evana (Cheltenham, UK Edward Elgar Publishing Limited, 2020)
Protecting Traditional Knowledge examines the emerging international frameworks for the protection of Indigenous traditional knowledge, and presents an analysis situated at the intersection between intellectual property, access and benefit sharing, and Indigenous peoples' rights to self-determination"--Back cover.
Traditional knowledge : why and how should we protect it? -- Biopiracy : shared history, different approaches -- Institutions and funds -- Access and benefit sharing -- Databases and registers -- Lessons from case studies.
Includes bibliographical references (pages 245-269) and index.
Keywords: Biopiracy -- Electronic books -- Government policy; Ethnoscience -- Government policy; Indigenous peoples -- Legal status, laws, etc; Cultural property -- Protection -- Law and legislation; Electronic books; Ethnoscience; Indigenous peoples -- Legal status, laws, etc; Cultural property -- Protection -- Law and legislation; Case studies